LBA9Real-world assessment of clinical effectiveness and safety of pazopanib in patients with advanced or metastatic renal cell carcinoma (RCC) in Asia, North Africa and Middle East countries: A prospective, observational study (PARACHUTE). (24th November 2019) - Kanesvaran, R; Biswas, B; Danchaivijitr, P; Lim, C S; Karabulut, B; Wong, Y F; Coskun, H S; Chang, C-H; Cicin, I; Ingles, S; Slimane, K; Erman, M
Abstract: Background: PARACHUTE, a phase IV, prospective, observational study of treatment patterns and outcomes planned to describe the clinical effectiveness and safety of pazopanib in patients (pts) with advanced or mRCC who are naïve to VEGF-TKI therapy in the real-life setting from Asia Pacific, North Africa, and the Middle East countries where data from the registration trials are lacking. Methods: Eligible pts were ≥18 years with advanced or mRCC and clinical decision to initiate pazopanib treatment or had already started new treatment with pazopanib within 15 days prior to study entry and naïve to any prior anti-VEGF therapy. Primary endpoint was the proportion of patients remaining progression free at 12 months (mo). The secondary endpoints were ORR, PFS, safety and tolerability, and relative dose intensity (RDI). Results: Between Jun 2017 and Dec 2018, 200 pts were enrolled from 15 countries in Asia, North Africa and Middle East. A total of 101 pts with a median age of 62 y (range, 32.0-95.0) were included in this interim analysis. Majority of the pts were Asian (63%) followed by Caucasian (36%). Clear cell was the main (82%) histologic type. At data cut-off (May 2, 2019) of 12 mo observation period, 29 pts completed the observational period and 72 discontinued the study. Only 57% of pts had the starting dose at 800mg. Median RDI was 79% with 52% pts received under <85%. 25 of 92 evaluable pts (27%) remained progression-free and median PFS was 4 mo (95% CI, 3.02-6.54). The best overall response per RECIST 1.1 is CR (2%), PR (18%) and SD (41%). 74% pts experienced ≥1 treatment related adverse event (TRAE) and 11% of pts discontinued due to TRAE. Most frequent (>10%) TRAEs include diarrhoea (27%), palmar-plantar erythrodysaesthesia syndrome (12%) and hypertension (15%). Conclusions: The interim results of the PARACHUTE study support the use of pazopanib in pts with advanced or mRCC who are naïve to VEGF-TKI therapy. Safety profile is consistent with the previously reported pivotal and realworld evidence studies. The efficacy data are still immature due to limited number of pts and the short follow-up duration. Editorial acknowledgement: Anuradha Bandaru, Novartis Healthcare Pvt Ltd (Hyderabad, India). Legal entity responsible for the study: Novartis. Funding: Has not received any funding. Disclosure: R. Kanesvaran: Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer, Novartis, MSD, BMS, Ipsen, Eisai, J&J, Astellas, Amgen, Mundipharma, Sanofi, Roche, AZ. P. Danchaivijitr: Advisory / Consultancy: MSD and Pfizer. B. Karabulut: Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck Serono, Bayer, Pfizer, Novartis, MSD, BMS, J&J, Astellas, Amgen, Sanofi, Roche. Y.F. Wong: Advisory / Consultancy: Merck and Roche. K. Slimane: Full / Part-time employment: Novartis. M. Erman: Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer, Novartis, BMS, Astellas, Roche, AstraZeneca, Boehringer Ingelheim, Nobel, Gen Pharma, MSD, Pierre Fabre, Amgen, Takeda, Mustafa Nevzat Pharma, Teva.